The Synergity Between of Centre Governmental Institution and Regional Governmental Institution in the Services of Basic Education - Mawar Mawar; Retnowati WD Tuti; Dini Gandini Purbaningrum; M. Sahrul (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose in this study is 1) How about condition and education quality at the border state of Sanggau Regency; 2) How about the institution synergity between centre government and region government in services of elementary school at Sanggau Regency. Research Methode in this study is to Descriptive, qualitative approach. Collecting data technique by observation, interview and documentation. The technique of collecting informan: Purposive and data accidental analysis by Macc Nabb. The result of tis study is Improving the quality of education at border area is an important step to strengthen the national defense system through education and culture.